2011
DOI: 10.1098/rspb.2011.0238
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of olfaction in non-avian theropod dinosaurs and birds

Abstract: Little is known about the olfactory capabilities of extinct basal (non-neornithine) birds or the evolutionary changes in olfaction that occurred from non-avian theropods through modern birds. Although modern birds are known to have diverse olfactory capabilities, olfaction is generally considered to have declined during avian evolution as visual and vestibular sensory enhancements occurred in association with flight. To test the hypothesis that olfaction diminished through avian evolution, we assessed relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
172
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(182 citation statements)
references
References 106 publications
(125 reference statements)
8
172
1
1
Order By: Relevance
“…However, the proportion of abventricular mitoses in the hyperpallium (proposed to be homologous to the dorsal cortex of mammals (Molnár and Butler, 2002)) is negligible compared to the proportions observed in the meso and nido‐pallium (Cheung et al, 2007). Even more relevant is that chickens and quails belong to a basal avian order (Galliformes) and zebra finch and parakeets to evolutionarily distant avian groups, the songbirds (order Passeriformes and Psittaciformes, respectively) (Zelenitsky et al, 2011). Thus, abventricular mitoses that occur in a well‐defined zone would be a derived evolutionary change occurring in these late avian orders.…”
Section: Is There An Svz With Intermediate Progenitors In the Sauropsmentioning
confidence: 99%
“…However, the proportion of abventricular mitoses in the hyperpallium (proposed to be homologous to the dorsal cortex of mammals (Molnár and Butler, 2002)) is negligible compared to the proportions observed in the meso and nido‐pallium (Cheung et al, 2007). Even more relevant is that chickens and quails belong to a basal avian order (Galliformes) and zebra finch and parakeets to evolutionarily distant avian groups, the songbirds (order Passeriformes and Psittaciformes, respectively) (Zelenitsky et al, 2011). Thus, abventricular mitoses that occur in a well‐defined zone would be a derived evolutionary change occurring in these late avian orders.…”
Section: Is There An Svz With Intermediate Progenitors In the Sauropsmentioning
confidence: 99%
“…Moreover an analysis of phylogenetic trends showed that the direct ancestors of modern birds did not show the modern bird's reduction in relative OB size, which must therefore be a secondary adaptation (55). This implies that carnivorous predators, whether diurnal theropods or nocturnal terrestrial mammals (40), are olfactory predictors, and require an enhanced OS system to track mobile, dispersed prey.…”
Section: Birdsmentioning
confidence: 99%
“…In a series of studies the olfactory ratio (ratio between olfactory bulb and cerebral hemisphere maximum diameters; OR values) were used as a proxy to study olfactory acuity and capacity in theropod dinosaurs (including birds) and crocodilians (Zelenitsky et al, 2009(Zelenitsky et al, , 2011. More recently this has also been applied to turtles (Paulina-Carabajal et al, 2017), showing that tortoises and meiolaniids (both terrestrial taxa) have the highest OR values (36-62 and 20-45%, respectively).…”
Section: Sensory Capabilities Of Proganochelysmentioning
confidence: 99%